Regularização fundiária urbana na Amazônia: um estudo do Programa Terra Legal nos Estados do Pará e do Amapá - OUTEIRO, Gabriel Moraes de (Universidade Federal do Pará, 2018)
In contemporary urban Brazil, with the increase of urban informality, land regularization is a fundamental issue in cities, especially in the Legal Amazon. Land regularization is an interdisciplinary process, that seeks to integrate irregular settlements into the legal context of cities, thus, protecting occupier ownership and engaging the local community in the urban policy debate. This study analyzes the Terra Legal Program of urban land regularization in the urban center of Serra do Navio/AP, in dispersed villages of Concórdia do Pará/PA and in an urban area of Tomé-Açu/PA, guided on neoinstitutionalism’s theoretical framework. The towns of Pará are settlements that are in transition from rural to urban space and the Tomé-Açu’s area is already consolidated, the district of Serra do Navio has historical and cultural importance. It is a qualitative research, in which a field study was carried out in these municipalities, as primary source. Secondary data source included official and institutional’s documents prepared during the execution of the land regularization project and public data. As a main result, it was verified that the Terra Legal Program is more characterized as an incremental adjustment within the same trajectory same trajectory of socio-spatial exclusion, with limited effects towards the democratization of access to land.